2022
DOI: 10.1186/s12940-022-00880-w
|View full text |Cite
|
Sign up to set email alerts
|

A process for creating data report-back tools to improve equity in environmental health

Abstract: Background Although there is increasing interest in reporting results of environmental research efforts back to participants, evidence-based tools have not yet been applied to developed materials to ensure their accessibility in terms of literacy, numeracy, and data visualization demand. Additionally, there is not yet guidance as to how to formally assess the created materials to assure a match with the intended audience. Methods Relying on formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The key differences between the prototype report pages were the community report centered around broad descriptions that reduced the number of technical terms and complex sentences, and contained more graphics, whereas the individual reports were focused on specific chemical categories and therefore contained more terminology that participants may have been unfamiliar with. Similar with the findings from this study, previous research has shown that barriers to understanding scientific materials, even if they were geared for a public audience, include insufficiently explained terminology, and complex sentence structures [ 38 ]. Thus, the revised reports reduced the use of technical terms when possible and the overall reading level, and used graphics to increase comprehension [ 39 ].…”
Section: Discussionsupporting
confidence: 87%
“…The key differences between the prototype report pages were the community report centered around broad descriptions that reduced the number of technical terms and complex sentences, and contained more graphics, whereas the individual reports were focused on specific chemical categories and therefore contained more terminology that participants may have been unfamiliar with. Similar with the findings from this study, previous research has shown that barriers to understanding scientific materials, even if they were geared for a public audience, include insufficiently explained terminology, and complex sentence structures [ 38 ]. Thus, the revised reports reduced the use of technical terms when possible and the overall reading level, and used graphics to increase comprehension [ 39 ].…”
Section: Discussionsupporting
confidence: 87%
“…who also engaged research participants to develop accessible report-back reports of indoor air quality data. 10 Given that personal air monitors generate information regarding times, locations, and activities associated with increased exposure, report-back may provide actionable information to guide personalized avoidance or intervention strategies Our study does have limitations that should be considered, including the limited racial diversity of EcoMAPPE participants and the completion of the follow-up questionnaire shortly after receiving the report-back document. In addition, adolescent participation rates were less than one-third of the total enrolled, likely due to incomplete or out-of-date contact information for some adolescent participants.…”
Section: Discussionmentioning
confidence: 99%
“…In June 2020, pregnant participants and those within 1 year postpartum completed a supplemental COVID-19 impact questionnaire, querying pandemic-related stress; infection history and precautions; and the Edinburgh Postnatal Depression Scale (EPDS) 96 97. Between May 2021 and August 2022, we deployed an Environmental Health Literacy (EHL) Questionnaire to ERGO participants who were at least a year postpartum, as part of a Harvard National Institute for Environmental Health Sciences centre-funded pilot study (P30ES000002) 98. The EHL Questionnaire included sections related to participants’ views on the environment (eg, phthalate exposure) and reproductive health, comfort with medical communications and personal health habits.…”
Section: Cohort Descriptionmentioning
confidence: 99%